Spirometric profile of people living with HIV on antiretroviral drugs in Abidjan - Kadiatou Samake; Z Koné; ATJ Daix; OAMC Akoun; DOC Kossa; AS Bakayoko; KMS Domoua (Journal of Respiratory Diseases, 2024)
Introduction People living with HIV (PLHIV) are susceptible to developing non- communicable chronic respiratory diseases. Our objective was to study the spirometric profile of this population. Material and methods This was a descriptive and analytical cross-sectional retro-prospective study conducted from March 15 to June 15, 2022 and relating to the analysis of the medical files of asymptomatic and eligible for spirometry PLHIV, aged 18 years and above. They were received in the voluntary counselling and testing (VCT) centres of one of the two pulmonology departments in Abidjan. Results The study involved 54 subjects including 22 men (40.7%) and 32 women (59.3%) with an average age of 48.9 years. The majority of patients were non-smokers (81.4%) and the main history was pulmonary tuberculosis (35.2%). Only 29.6% had chronic respiratory symptoms and 42.6% had a normal BMI. The frequency of spirometric abnormalities was 57.4%. These spirometric abnormalities included 40.7% peripheral obstructive pattern; 9.3% restrictive pattern; 3.7% asthma and 3.7% COPD. A more than 10 years duration of HIV infection (p=0.001 OR= 0.2 (0.1 – 0.7)) and a duration of ART of at least 10 years (p=0.001 OR= 0, 2 (0.1 – 0.7)) were significantly associated with the existence of ventilatory abnormalities. Conclusion The high frequency of ventilatory anomalies in PLHIV independently of the existence of chronic respiratory signs leads us to propose spirometry in the follow-up assessment of PLHIV while paying particular attention to those on ARVs for more than 10 years.
Keywords: Profile